2017
DOI: 10.1145/3090089
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Person-to-person Proximity Using WiFi Signals

Abstract: Today's societies are enveloped in an ever-growing telecommunication infrastructure. This infrastructure offers important opportunities for sensing and recording a multitude of human behaviors. Human mobility patterns are a prominent example of such a behavior which has been studied based on cell phone towers, Bluetooth beacons, and WiFi networks as proxies for location. However, while mobility is an important aspect of human behavior, understanding complex social systems requires studying not only the movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 56 publications
0
62
0
Order By: Relevance
“…On the other side, Bluetooth-based study [29] is one of the earliest attempts for localization in indoor environments. However, Bluetooth scanning is power hungry [10]. Moreover, many of the Android smartphones (starting from versions 4.4) have partial support for Bluetooth Low-Energy (BLE), which are capable of only detecting other BLE devices [16].…”
Section: Location Proximitymentioning
confidence: 99%
See 3 more Smart Citations
“…On the other side, Bluetooth-based study [29] is one of the earliest attempts for localization in indoor environments. However, Bluetooth scanning is power hungry [10]. Moreover, many of the Android smartphones (starting from versions 4.4) have partial support for Bluetooth Low-Energy (BLE), which are capable of only detecting other BLE devices [16].…”
Section: Location Proximitymentioning
confidence: 99%
“…In this line, we capture different types of real-life meeting group scenarios such as outdoor roadside informal meeting; informal outdoor cafe meet, formal and informal laboratory meeting, and classroom interaction as shown in Figure 1. Das Identification of a meeting group primarily relies on the location proximity [9], [10] of the group members, which (apparently) can be conceptualized as a localization problem [11], [12]. In that direction, prior art explores the following three modalities -GPS, Bluetooth, and WiFi for identification of the location similarity in supervised [10] as well as unsupervised [13] manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…a More recently, Sapiezynski [28] proposed a model to infer person-to-person proximity by using WiFi signals. Sekara and Lehmann [29] studied how to deploy the electronic datasets as a valid proxy for real life social interactions, and found that the strength of electronic signals can be used to distinguish between strong and weak friendship ties.…”
Section: Social Behaviormentioning
confidence: 99%